ANALISIS DAN IMPLEMENTASI SISTEM KONTROL LAMPU RUMAH OTOMATIS MENGGUNAKAN METODE FUZZY LOGIC - I Made Alit Dwi Saputra; Ilham Julian Efendi; Subardin (Program Studi Ilmu Komputer FMIPA-UHO, 2025)
Efficient use of electrical energy is one of the important aspects in a smart home system. One solution is an automatic lighting control system that can turn lights on or off based on environmental conditions. This study aims to design and implement an automatic home lighting control system using the Mamdani fuzzy logic inference method, with the integration of the Internet of Things (IoT) through the Blynk application for remote monitoring and control. This system usesanLDR sensor to detect environmental lighting levels and a PIR sensor to detect human movement. Data from the sensors is processed using predetermined rule-based fuzzy logic to produce lighting control decisions (ON or OFF). The implementation offuzzy logic is carried out on an Arduino microcontroller, while IoT connectivity and user interface are handled by the ESP8266 module connected to the Blynk platform. The test results show that the system can work automatically with responsiveness and accuracy. The lights turn on only when the light is dim/dark and there is movement, and can be controlled manually through the Blynk application. This system also allows monitoring ofsensor values (LDR and PIR) in real time via mobile devices. With the integration offuzzy logic and IoT, the system is proven to be effective in improving energy efficiency and user comfort in the home environment